PENGARUH MOTIVASI, DISIPLIN DAN KEPUASAN TERHADAP KINERJA PEGAWAI (Studi Kasus Pada Pegawai PT. ANUGERAH PUTRA SIANTAN Songsong Singosari Malang) - Winarno Winarno; Hadi Sunaryo (UNIVERSITAS ISLAM MALANG, 2017)
AbstractThis study aims to examine the influence of motivation, discipline,satisfaction on the performance of employees of PT. ANUGERAH PUTRASIANTAN Songsong Singosari Malang. The research was conducted by usingexplanatory method with quantitative method on PT. ANUGERAH PUTERASIANTAN Songsong Singosari Malang. Data collection was done by distributingquestionnaires to respondents. Questionnaires were distributed to 57 productionemployees. The analysis tool used is multiple linear regression. The results ofresearch show that the description of the research results showed that employeejob satisfaction influence on employee performance, work discipline employeesaffect employee performance, employee motivation has no effect on performance.Keywords: Motivation, Discipline, Satisfaction and employee performance.